PENGARUH KEMAMPUAN TEKNIK PEMAKAI SISTEM INFORMASI AKUNTANSI, PARTISIPASI MANAJEMEN, EFEKTIVITAS DAN TECHNOSTRESS TERHADAP KINERJA INDIVIDU PADA PT ASATECH INDONESIA GROUP PALEMBANG - Nyimas (Jurnal Keuangan dan Bisnis, 2019)
Individual performance is the success of a company, it is expected that individuals can complete the task on time. In order to achieve good individual performance, an organization should consider the factors which influence it. The purpose of this study was to identify technical capabilities of accounting information system’s users, management participation, efectiveness and technostress toward individual performance. This research was conducted at PT Asatech Indonesia Group Palembang which involved 100 employees as the sample of study. They were selected by using purposive sampling technique. The data was collected by administering questionnaire and analyzed by using multiple linear regression analysis The results revealed that technical capabilities of accounting information system’s users, management participation, effectiveness and technostress had significant effect on individual performance.